MAKNA RITUAL KUNGKUM DI UMBUL NYAI KENDAT PLUMBUNGAN KABUPATEN BAYOLALI PERSPEKTIF AGAMA HINDU - Farida Setyaningsih (Widya Aksara, 2020)
Kungkum ritual is a method of union between Atman and Brahman through the Meditation method in water. Kungkum focuses his concentration on the Sapta Cakra that is in the human body to activate these chakras with the aim of getting closer to God. When the chakras in the human body eat many benefits both medically and non-medically, scale and niskala. By using the concept of function in the Hindu tradition, this study discusses the procedures, meanings and values ??contained in the Kungkum ritual which is a Hindu Tradition, which is to gush or purify a person through certain practices. In discussing the meaning of kungkum ritual in Hindu tradition. Discussion of the procedures and benefits of using functions, while the meaning will be discussed on the basis of symbol theory. Kungkum rituals performed by humans in Umbul Nyai Kendat are not much different from kungkum rituals in several places. The aim of Kungkum at Umbul Nyai Kendat is to unite Atman with the Brahman within himself through the water method as a means of concentration. Concentrate on Kungkum by opening the aura that is in our body / doer which is centered on the Chakras in the body. When the chakras are active, someone who does kungkum will get many benefits such as not getting sick easily, being more sensitive to astral things and so on. After knowing the Meaning of Kungkum Rituals in Hindu Traditions, it is expected that all parties should help preserve the existence of Kungkum as a means of self-purification. This is a form of ancestral heritage that needs to be maintained. This is to add to the richness of Hindu culture and traditions that are almost extinct. After this research it is hoped that further research will emerge regarding rituals, ceremonies and ceremonies as well as ethics carried out by the community.